DEVELOPMENT OF DIFFERENTIATED LEARNING E-MODULES TO IMPROVE FIFTH GRADE SOCIAL STUDIES LEARNING OUTCOMES - Marlina Yosi Yanti; Siti Aisyah; Hendrizal (Universitas Majalengka, 2025)
This study aims to develop an E-module based on differentiated learning and to examine its validity, practicality, and effectiveness in improving elementary school students’ social studies learning outcomes. The research is motivated by the limited use of technology in social studies instruction and the absence of digital modules that align with students’ characteristics and learning styles. The study employs a Research and Development (R&D) method using the 4D model, which includes the stages of Define, Design, Develop, and Disseminate. The research subjects consist of experimental and control class students, teachers as respondents, and expert validators in content, media, and language. Data were collected through observation, questionnaires, tests, interviews, and documentation. The results show that the developed E-module is highly valid based on expert assessments, very practical according to teacher and student responses, and effective in improving social studies learning outcomes, with an average N-Gain score of 77.88 categorized as high. This e-module is suitable for use as an alternative teaching material in social studies learning in elementary schools.